The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1093/oxfordjournals.eurheartj.a060082
|View full text |Cite
|
Sign up to set email alerts
|

Infective right atrial thrombus: a rare complication of total parenteral nutrition in an adult

Abstract: We describe a case of an infective right atrial thrombus, following total parenteral nutrition, in a 21-year-old woman undergoing a surgical procedure for long-standing chronic ulcerative colitis. She presented with high temperature and the illness did not respond to antibiotic therapy. A 2-dimensional echocardiogram showed a mobile right atrial mass that at surgery was identified as a thrombus. Thrombus cultures grew coagulase-negative Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…20 Although our observational study does not elucidate underlying mechanisms accounting for these sex differences, recent studies have suggested that myocyte hypertrophy due to an increase in aortic stiffness and enhanced afterload in older subjects may account for an age-dependent increase in LVEF. 5,[21][22][23] Furthermore, a progressive myocyte loss in aged men, but not in women, was observed in a postmortem analysis and may account for the sex differences in LV function. 24 Reduced testosterone levels and reduced physical activity in older men have been suggested to account for these findings.…”
Section: Discussionmentioning
confidence: 87%
“…20 Although our observational study does not elucidate underlying mechanisms accounting for these sex differences, recent studies have suggested that myocyte hypertrophy due to an increase in aortic stiffness and enhanced afterload in older subjects may account for an age-dependent increase in LVEF. 5,[21][22][23] Furthermore, a progressive myocyte loss in aged men, but not in women, was observed in a postmortem analysis and may account for the sex differences in LV function. 24 Reduced testosterone levels and reduced physical activity in older men have been suggested to account for these findings.…”
Section: Discussionmentioning
confidence: 87%